(untitled) (Global Journal of Management and Business Research, 2021)
The present work begins with the development of the concept of what is the factorial analysis mentioning and defining the concept, as well as some uses such as the reduction of dimensions, by the use of many and different variables, which may affect a subject to study. The next part is devoted to the use of the multivariate statistical technique with an independent approach in eco-innovation studies, that is, factor analysis and ecoinnovation. This section mentions the fact that in studies related to eco-innovation the works that have been carried out are of the qualitative type and the quantitative ones are very scarce or almost null, in relation to the use of factorial analysis.